Le cadre politico-institutionnel des migrations antillaises : des dynamiques différenciées dans un contexte géopolitique segmenté - Cédric Audebert (Études Caribéennes)
The making of Caribbean societies is indissociable from long-term migration movements. The favourable politico-legal framework of Caribbean migrations towards their metropoles accounts for the strength of migration streams from politically dependent territories in the region. It also accounts for their spatial configuration as ‘migratory couples’. The issue is different as far as independent territories are concerned. The analysis of three Caribbean populations – Puerto Ricans, French West Indians, Haitians – questions the particularity of the politico-institutional contexts of source societies in relation with the singular modalities of their colonization. Given the remarkable diversity of political statuses in the Caribbean, the analysis of the relation between migration and the colonial history requires to question the influence of these statuses on the temporality, the scale, the composition and the spatialization of population movements.